Preparation method of reduced graphene oxide loaded metal cluster / single atom
By rapid thermal solution of plastic and metal compounds under the inflow of hydrogen -free atmosphere, prepare a reduction of oxygenyl oxygenne load metal cluster/single atomic material, solve the safety and cost problem of traditional plastic thermal solution methods, and achieve efficient plastic plastics Waste treatment and production of high value -added products.
Patent Information
- Application Number
- CN202411496239.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-28
AI Technical Summary
Traditional plastic pyrolysis methods are low in safety, high in cost, easy to cause secondary pollution, and the products are difficult to further apply, which cannot efficiently solve the problem of plastic waste treatment.
Adopt the preparation method of restore oxygenne load metal cluster/single atomic material. By physical mixing plastic and metal compounds, and rapid heat solution under the surround of hydrogen -free atmosphere, preparing materials with thin thickness, large yield, and wide application materials are prepared Essence
In the realization of the hydrogen -free atmosphere, it is quickly and efficiently prepared to restore the reduction of oxygenylite loaded metal clusters/single atomic materials, solve the problem of plastic pollution, and generate high value -added products at the same time, suitable for industrialized scale production.
Smart Images

Figure HDA0005102027270000011 
Figure HDA0005102027270000012 
Figure HDA0005102027270000021
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inorganic nano and polymer materials, and in particular to a method for preparing reduced graphene oxide loaded metal clusters / single atom materials. Background Art
[0002] Plastics are widely used in all walks of life due to their low cost, light weight, durability and processability. So far, a variety of polymers including polyethylene, polypropylene, polyvinyl chloride, polyethylene terephthalate and polystyrene have been used to make commercial plastics. With the rapid growth of plastic production, a large amount of solid waste is also generated every year. Since these plastic wastes have ultra-high chemical stability, they are difficult to degrade naturally. Therefore, it is of great practical significance to seek an efficient and rapid method to convert plastic waste into high-value-added materials. However, plastics need to be pyrolyzed in a hydrogen atmosphere. The pyrolysis process is very slow and easily produces a large amount of harmful gases, and its products are usually difficult to further apply; therefore, the traditional plastic pyrolysis method has low safety, high cost, and is prone to secondary pollution. Summary of the invention
[0003] In view of this, the present invention provides a method for preparing reduced graphene oxide-loaded metal clusters / single atom materials. The preparation method provided in the present application is fast, simple and convenient, and can prepare reduced graphene oxide-loaded metal clusters / single atom materials from waste plastics. The obtained material has a thin thickness, a large output, and a wide application, and is suitable for industrial-scale production.
[0004] Reduced graphene oxide loaded metal clusters / single atom materials have unique electronic properties, excellent electrical conductivity, and good physical and chemical properties. They are widely used in fuel cells, water electrolysis to produce hydrogen, electrocatalytic redox reactions, electrobiosensing, organic catalytic conversion, and other fields. Compared with ordinary reduced graphene oxide, reduced graphene oxide loaded metal clusters / single atom materials can not only retain the excellent properties of reduced graphene oxide, but also the synergistic effect between the two can make the composite material show more superior performance. In addition, the insertion of metal clusters / single atoms between graphene sheets can reduce the intermolecular forces between reduced graphene oxide sheets, effectively avoid the aggregation of reduced graphene oxide sheets, enhance the activity of metal nanoparticles, and ultimately improve the material properties.
[0005] The applicant uses metal compounds and plastics as raw materials, and can greatly shorten the plastic pyrolysis time and improve the efficiency of plastic pyrolysis in a hydrogen-free atmosphere through a rapid heating process; at the same time, the thermal radiation generated during the extremely rapid heating process can cause the high-stability structure of the plastic to undergo significant changes. Therefore, using plastics or waste plastics and metal compounds as raw materials, the rapid pyrolysis technology can quickly and efficiently prepare reduced graphene oxide-loaded metal clusters / single atom materials in a hydrogen-free atmosphere, which can not only solve the problem of plastic pollution, but also produce high value-added products.
[0006] Based on this, the present application provides a method for preparing reduced graphene oxide-loaded metal clusters / single atom materials, comprising the following steps:
[0007] a) physically mixing the plastic and the metal compound to obtain a solid mixed raw material;
[0008] b) rapidly pyrolyzing the solid mixed raw material in a hydrogen-free atmosphere to obtain reduced graphene oxide-supported metal clusters / single atom materials.
[0009] In some specific implementations, the plastic is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate, polycarbonate, polyvinyl chloride, or polystyrene;
[0010] The metal compound is selected from at least one of metal oxides, chlorides, nitrates or acetylacetonates;
[0011] The metal is selected from at least one of iron, cobalt, nickel, copper, zinc, gold, silver, platinum, palladium, iridium, ruthenium or rhodium.
[0012] In some specific implementations, the plastic is plastic waste.
[0013] In some specific implementations, the mass ratio of the plastic to the metal compound is 0.05 to 4:1.
[0014] In some specific implementations, the plastic is plastic particles, and the diameter of the plastic particles is 1 μm to 3 mm;
[0015] The metal compound is metal compound powder.
[0016] In some specific implementations, the step b) specifically includes the following steps:
[0017] The solid mixed raw material is added into a Joule heating device, and an inert gas is introduced to exclude air; under the condition of introducing the inert gas, the solid mixed raw material is rapidly pyrolyzed in a hydrogen-free atmosphere to obtain reduced graphene oxide loaded metal clusters / single atom materials.
[0018] In some specific implementations, the inert gas is selected from argon or nitrogen;
[0019] The flow rate of the inert gas is 50 mL / min to 300 mL / min.
[0020] In some specific implementations, the temperature of the pyrolysis treatment is 300° C. to 1200° C., the heating rate is 50° C. / s to 2000° C. / s, and the time is 0.5 min to 15 min.
[0021] In some specific implementations, the step b) further includes the following steps:
[0022] The reaction product obtained by pyrolysis is washed and separated, and the obtained solid is dried to obtain reduced graphene oxide loaded metal clusters / single atom materials.
[0023] In some specific implementations, the washing is performed by using hydrochloric acid; the separation is performed by suction filtration; and the drying temperature is 50° C. to 100° C.
[0024] The preparation method of reduced graphene oxide loaded metal clusters / single atom materials provided in the present application comprises the following steps: a) physically mixing plastic and metal compounds to obtain a solid mixed raw material; b) rapidly pyrolyzing the solid mixed raw material in a hydrogen-free atmosphere to obtain reduced graphene oxide loaded metal clusters / single atom materials. The present application uses plastic or plastic waste and metal compounds as raw materials, and rapid pyrolysis in a hydrogen-free atmosphere can prepare reduced graphene oxide loaded metal clusters / single atom materials. The synthesis method is fast, simple, and convenient. The obtained reduced graphene oxide loaded metal clusters / single atom materials are thin in thickness, large in yield, and widely used in products, and are suitable for industrial-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0026] Figure 1 This is a transmission electron microscope image of the product obtained in Example 1 of the present invention;
[0027] Figure 2 This is an atomic force microscope image of the product obtained in Example 1 of the present invention;
[0028] Figure 3 This is the X-ray diffraction pattern of the product obtained in Example 1 of the present invention;
[0029] Figure 4 This is the infrared spectrum of the product obtained in Example 1 of the present invention;
[0030] Figure 5 This is a Raman spectrum of the product obtained in Example 1 of the present invention;
[0031] Figure 6 is an X-ray photoelectron spectrum of oxygen in the product obtained in Example 1 of the present invention;
[0032] Figure 7 This is an X-ray photoelectron spectrum of carbon in the product obtained in Example 1 of the present invention;
[0033] Figure 8 This is a high-angle annular dark-field scanning transmission microscope image of the product obtained in Example 1 of the present invention;
[0034] Fig. 9 This is an energy dispersive X-ray spectrum of the product obtained in Example 1 of the present invention;
[0035] Fig.10 This is a transmission electron microscope image of the product obtained in Example 2 of the present invention;
[0036] Fig.11 This is an atomic force microscope image of the product obtained in Example 2 of the present invention;
[0037] Fig.12 This is the X-ray diffraction pattern of the product obtained in Example 2 of the present invention;
[0038] Fig.13 This is the infrared spectrum of the product obtained in Example 2 of the present invention;
[0039] Fig.14 This is a Raman spectrum of the product obtained in Example 2 of the present invention;
[0040] Fig.15 This is an X-ray photoelectron spectrum of oxygen in the product obtained in Example 2 of the present invention;
[0041] Fig.16 This is an X-ray photoelectron spectrum of carbon in the product obtained in Example 2 of the present invention;
[0042] Fig.17 This is a high-angle annular dark-field scanning transmission microscope image of the product obtained in Example 2 of the present invention;
[0043] Fig.18 This is an energy dispersive X-ray spectrum of the product obtained in Example 2 of the present invention;
[0044] Fig.19 This is a transmission electron microscope image of the product obtained in Example 3 of the present invention;
[0045] Fig. 20 This is an atomic force microscope image of the product obtained in Example 3 of the present invention;
[0046] Fig.21 This is the X-ray diffraction pattern of the product obtained in Example 3 of the present invention;
[0047] Fig. 22 This is the infrared spectrum of the product obtained in Example 3 of the present invention;
[0048] Fig.23 This is a Raman spectrum of the product obtained in Example 3 of the present invention;
[0049] Fig.24 This is an X-ray photoelectron spectrum of oxygen in the product obtained in Example 3 of the present invention;
[0050] Fig.25 This is an X-ray photoelectron spectrum of carbon in the product obtained in Example 3 of the present invention;
[0051] Fig.26 This is a high-angle annular dark-field scanning transmission microscope image of the product obtained in Example 3 of the present invention;
[0052] Fig. 27 This is an energy dispersive X-ray spectrum of the product obtained in Example 3 of the present invention;
[0053] Fig.28 This is a transmission electron microscope image of the product obtained in Example 4 of the present invention;
[0054] Fig.29 This is an atomic force microscope image of the product obtained in Example 4 of the present invention;
[0055] Fig.30 This is the X-ray diffraction pattern of the product obtained in Example 4 of the present invention;
[0056] Fig.31 This is the infrared spectrum of the product obtained in Example 4 of the present invention;
[0057] Fig.32 This is a Raman spectrum of the product obtained in Example 4 of the present invention;
[0058] Fig.33 This is an X-ray photoelectron spectrum of oxygen in the product obtained in Example 4 of the present invention;
[0059] Fig.34 This is an X-ray photoelectron spectrum of carbon in the product obtained in Example 4 of the present invention;
[0060] Fig.35 This is a high-angle annular dark-field scanning transmission microscope image of the product obtained in Example 4 of the present invention;
[0061] Fig.36 This is an energy dispersive X-ray spectrum of the product obtained in Example 4 of the present invention.
[0062] Fig.37 This is a transmission electron microscope image of the product obtained in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0063] It should be understood that the expression "one or more of..." includes each of the items recited after the expression individually and in various different combinations of two or more of the recited items, unless otherwise understood from the context and usage. The expression "and / or" in combination with three or more recited items should be understood to have the same meaning, unless otherwise understood from the context.
[0064] The use of the terms "comprising", "having" or "containing", including their grammatical synonyms, should generally be understood as open and non-restrictive, for example not excluding other unrecited elements or steps, unless otherwise specifically stated or otherwise understood from the context.
[0065] It should be understood that the order of steps or the order in which certain actions are performed is not important as long as the present invention remains operable. In addition, two or more steps or actions may be performed simultaneously.
[0066] The use of any and all examples or exemplary language, such as "for example" or "including", herein is intended only to better illustrate the invention and does not limit the scope of the invention unless otherwise claimed. No language in this specification should be construed as indicating that any non-claimed element is essential to the practice of the invention.
[0067] In addition, the numerical ranges and parameters used to define the present invention are approximate values, and the relevant values in the specific embodiments have been presented as accurately as possible. However, any numerical value inherently inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise expressly stated, it should be understood that all ranges, quantities, values and percentages used in this disclosure are modified by "about". Here, "about" generally means that the actual value is within plus or minus 10%, 5%, 1% or 0.5% of a specific value or range.
[0068] The present application provides a method for preparing a reduced graphene oxide-loaded metal cluster / single atom material, comprising the following steps:
[0069] a) physically mixing the plastic and the metal compound to obtain a solid mixed raw material;
[0070] b) rapidly pyrolyzing the solid mixed raw material in a hydrogen-free atmosphere to obtain reduced graphene oxide-supported metal clusters / single atom materials.
[0071] The present application uses plastic or plastic waste and metal compounds as raw materials, and can prepare reduced graphene oxide-loaded metal clusters / single atom materials by rapid pyrolysis in a hydrogen-free atmosphere. The synthesis method is fast, simple and convenient. The prepared reduced graphene oxide-loaded metal clusters / single atom materials are thin in thickness, large in yield, and have wide product applications, and are suitable for industrial-scale production.
[0072] The present application uses plastic as raw material, which can be plastic or plastic waste, preferably plastic waste, which can not only solve the problem of plastic pollution, but also produce high value-added products. The present application has no special restrictions on the types of the plastic or plastic waste, including but not limited to carbon-containing products such as polyethylene, polypropylene, polyethylene terephthalate, polycarbonate, polyvinyl chloride or polystyrene, which can be one or more of them; when the plastic is a variety of them, the present application has no special restrictions on the dosage ratio of each specific substance. In some specific implementations, the plastic or plastic waste is preferably plastic particles or plastic waste sheets. In some specific implementations, the particle size of the plastic particles or plastic waste sheets is 1μm to 3mm, preferably 50μm to 2.5mm, and more preferably 100μm to 2mm. The present application has no special restrictions on the source of the waste or plastic waste, and plastic products or plastic waste purchased or recycled on the market can be used.
[0073] The present application uses metal compounds as raw materials, and the metal compounds include but are not limited to metal oxides, chlorides, nitrates or acetylacetonates, which can be one or more of them; the metals include but are not limited to iron, cobalt, nickel, copper, zinc, gold, silver, platinum, palladium, iridium, ruthenium or rhodium, etc., which can be one or more of them. Typical metal compounds include but are not limited to zinc oxide, ferrous oxide, cupric oxide, etc. When the metal compound is a combination of multiple substances, the present application has no special restrictions on the content of each specific substance. In some specific implementations, the metal compound is a powder.
[0074] The present application first mixes plastic or plastic waste with a metal compound to obtain a solid mixed raw material. The present application has no restrictions on the mixing method, for example, the plastic or plastic waste and the metal compound are directly mixed in a grinder or agitator under grinding or stirring conditions until they are uniformly mixed. In some specific implementations, the mass ratio of the plastic to the metal compound is 0.05 to 4:1. Preferably, it is 0.1 to 3.5:1, more preferably 0.2 to 3:1, and most preferably 0.25:1.
[0075] After the plastic or plastic waste and the metal compound are uniformly mixed, they are rapidly heated in a hydrogen-free atmosphere to pyrolyze the plastic or plastic waste and the metal compound. In some specific implementations, the rapid heating treatment Joule heat treatment is a technology that can achieve thermal conversion of materials by rapidly heating up a Joule heating device, and the material treatment is achieved by controlling the heating rate of the reaction furnace, the heat treatment temperature and the heat treatment time.
[0076] Specifically, the step b) may include the following steps:
[0077] The solid mixed raw material is added into a Joule heating device, and an inert gas is introduced to exclude air; under the condition of introducing the inert gas, the solid mixed raw material is pyrolyzed in a hydrogen-free atmosphere to obtain reduced graphene oxide loaded metal clusters / single atom materials.
[0078] The present application has no special restrictions on the Joule heating device, and any Joule heat reactor purchased on the market can be used. After obtaining the solid mixed raw material, the present application adds it to the Joule heat reactor. Specifically, the solid mixed raw material can be first added to the container of the Joule heat reactor, such as a quartz boat, a graphite boat, a corundum boat, etc., and then the container is placed in the Joule heat reactor. The present application has no special restrictions on the amount of the solid mixed raw material added, for example, it can be 0.075g to 1000g, which can be adjusted according to the maximum loading capacity of the Joule heat reactor.
[0079] Before heating the Joule heat reaction furnace, an inert gas is first introduced to remove the air in the furnace. In some specific implementations, the inert gas is selected from argon or nitrogen, preferably nitrogen. In some specific implementations, the flow rate of the inert gas is 50mL / min to 300mL / min, preferably 100mL / min to 250mL / min, and more preferably 150mL / min to 200mL / min. The present application has no special restrictions on the source of the inert gas, and commercially available compressed nitrogen or compressed argon can be directly used.
[0080] After the air in the furnace is removed, the solid mixed raw material is rapidly heated under the condition of passing an inert gas. In some specific implementations, the inert gas is selected from argon or nitrogen, preferably nitrogen. In some specific implementations, the flow rate of the inert gas is 50mL / min to 300mL / min, preferably 100mL / min to 250mL / min, and more preferably 150mL / min to 200mL / min. In some specific implementations, the heating rate of the reactor is 50℃ / s to 2000℃ / s, preferably 80℃ / s to 1500℃ / s, and more preferably 100℃ / s to 1000℃ / s. It can be understood by those skilled in the art that the heating rate of the reactor is the heating rate of the solid mixed raw material for rapid heating. In some specific implementations, the temperature of the heat treatment is 300°C to 1200°C, preferably 500°C to 1100°C, more preferably 800°C to 1000°C, and the time is 0.5min to 15min, preferably 0.8min to 10min, more preferably 1min to 5min. It is understood that the temperature and time of the rapid heating treatment are the final temperature and holding time of the reaction furnace.
[0081] After the reaction is completed, the obtained reaction product is washed and separated, and the obtained solid is dried to obtain reduced graphene oxide loaded metal clusters / monoatom materials. The present application preferably uses hydrochloric acid to wash the obtained reaction product, and the number of washings can be multiple times, the purpose is to remove the residual metal ions in the reaction product. After washing, the obtained product is filtered, and the product is preferably separated by suction filtration to obtain a solid, and the obtained solid is dried to obtain reduced graphene oxide loaded metal clusters / monoatom materials. In some specific implementations, the drying can be carried out in a drying oven, and the drying temperature is 50°C to 100°C, preferably 80°C. The present application has no special restrictions on the drying time, and all the moisture in the obtained solid can be dried.
[0082] In some specific implementations, the present application recycles the waste liquid after washing for recycling. Specifically, the present application dries the waste liquid after washing to obtain a recovered solid. The drying temperature is 40°C to 100°C, preferably 60°C. The present application has no special restrictions on the drying time, and all the water in the obtained waste liquid can be dried.
[0083] The preparation method provided in the present application is simple to operate, fast and efficient, and a single batch of metal clusters / single atom materials supported by reduced graphene oxide can be obtained in only 1 minute. Moreover, the method can be further scaled up according to the equipment size to prepare higher yields of metal clusters / single atom materials supported by reduced graphene oxide.
[0084] The preparation method of the reduced graphene oxide-loaded metal cluster / single atom material provided in the present application is further described below in conjunction with the examples.
[0085] Example 1
[0086] 7.5 g of polyethylene terephthalate and 150 g of zinc oxide powder are physically mixed to obtain a mixed solid raw material; the mixed solid raw material is loaded into a special quartz boat, and the quartz boat is placed in a reaction furnace;
[0087] Argon gas is introduced into the reactor at a flow rate of 180 mL / min to exclude air in the reactor chamber, and the air exclusion time is 3 minutes. After the air is excluded, argon gas is continuously introduced until the reaction is completed; the heating rate of the reactor is 100° C. / s, the reaction temperature is 1000° C., and the reaction time is 1 minute; after the reaction is completed, the obtained product is washed with hydrochloric acid several times to remove residual zinc ions, filtered and separated to obtain a solid, and the obtained solid is dried in a drying oven at 80° C. to obtain a black powder, i.e., zinc clusters loaded with reduced graphene oxide; after the washing is completed, the waste liquid is recovered and dried in a drying oven at 60° C. to obtain a solid material, and the obtained solid material can be used as a raw material for the next reaction.
[0088] The black powder prepared in Example 1 was subjected to structural identification, and the results are shown in Figures 1 to 9 , Figure 1 This is a transmission electron microscope image of the product obtained in Example 1 of the present invention; Figure 2 This is an atomic force microscope image of the product obtained in Example 1 of the present invention; Figure 3 This is the X-ray diffraction pattern of the product obtained in Example 1 of the present invention; Figure 4 This is the infrared spectrum of the product obtained in Example 1 of the present invention; Figure 5 This is a Raman spectrum of the product obtained in Example 1 of the present invention; Figure 6 The X-ray photoelectron spectrum of oxygen in the product obtained in Example 1 of the present invention; Figure 7 The X-ray photoelectron spectrum of carbon in the product obtained in Example 1 of the present invention; Figure 8 This is a high-angle annular dark-field scanning transmission microscope image of the product obtained in Example 1 of the present invention; Fig. 9 This is an energy dispersive X-ray spectrum of the product obtained in Example 1 of the present invention.
[0089] Figure 1 and Figure 2 It was shown that the obtained product was an ultrathin two-dimensional material; Figure 3 The X-ray diffraction pattern shows that the obtained product is a carbon material; Figures 3 to 7 It was shown that the obtained product was reduced graphene oxide; Figure 8 It showed the presence of metal clusters in the obtained product; Fig. 9The clusters present in the obtained product are zinc clusters. Figures 1 to 9 It can be seen that the product synthesized in Example 1 is zinc clusters supported by reduced graphene oxide.
[0090] Example 2
[0091] 7.5 g of polyethylene terephthalate and 30 g of ferrous oxide powder are physically mixed to obtain a mixed solid raw material; the mixed solid raw material is loaded into a special quartz boat, and the quartz boat is placed in a reaction furnace;
[0092] Argon gas is introduced into the reactor at a flow rate of 180 mL / min to exclude air in the reactor chamber, and the air exclusion time is 3 minutes. After the air is excluded, argon gas is continuously introduced until the reaction is completed; the heating rate of the reactor is 100° C. / s, the reaction temperature is 1000° C., and the reaction time is 1 minute; after the reaction is completed, the obtained product is washed with hydrochloric acid several times to remove residual iron ions, filtered and separated to obtain a solid, and the obtained solid is dried in a drying oven at 80° C. to obtain a black powder, i.e., iron clusters loaded with reduced graphene oxide; after the washing is completed, the waste liquid is recovered and dried in a drying oven at 60° C. to obtain a solid material, and the obtained solid material can be used as a raw material for the next reaction.
[0093] The structure of the compound prepared in the example was identified. Figures 10 to 18 , Fig.10 This is a transmission electron microscope image of the product obtained in Example 2 of the present invention; Fig.11 This is an atomic force microscope image of the product obtained in Example 2 of the present invention; Fig.12 This is the X-ray diffraction pattern of the product obtained in Example 2 of the present invention; Fig.13 This is the infrared spectrum of the product obtained in Example 2 of the present invention; Fig.14 This is a Raman spectrum of the product obtained in Example 2 of the present invention; Fig.15 The X-ray photoelectron spectrum of oxygen in the product obtained in Example 2 of the present invention; Fig.16 The X-ray photoelectron spectrum of carbon in the product obtained in Example 2 of the present invention; Fig.17 This is a high-angle annular dark-field scanning transmission microscope image of the product obtained in Example 2 of the present invention; Fig.18 This is an energy dispersive X-ray spectrum of the product obtained in Example 2 of the present invention;
[0094] Fig.10 and Fig.11 It was shown that the obtained product was an ultrathin two-dimensional material; Fig.12 The X-ray diffraction pattern shows that the obtained product is a carbon material; Figures 13-16 It was shown that the obtained product was reduced graphene oxide; Fig.17 It showed the presence of metal clusters in the obtained product; Fig.18The clusters present in the obtained product are iron clusters. Figures 10 to 18 It can be seen that the product synthesized in Example 2 is iron clusters supported by reduced graphene oxide.
[0095] Example 3
[0096] 7.5 g of polyethylene terephthalate and 30 g of cuprous oxide powder are physically mixed to obtain a mixed solid raw material; the mixed solid raw material is loaded into a special quartz boat, and the quartz boat is placed in a reaction furnace;
[0097] Argon gas is introduced into the reactor at a flow rate of 180 mL / min to exclude air in the reactor chamber, and the air exclusion time is 3 minutes. After the air is excluded, argon gas is continuously introduced until the reaction is completed; the heating rate of the reactor is 100°C / s, the reaction temperature is set to 1000°C, and the reaction time is set to 10 minutes; after the reaction is completed, the obtained product is washed with hydrochloric acid several times to remove residual copper ions, and the solid is separated by suction filtration, and the obtained solid is dried in a drying oven at 80°C to obtain a black powder, i.e., copper single atoms loaded on reduced graphene oxide; after the washing is completed, the waste liquid is recovered and dried in a drying oven at 60°C to obtain a solid material, and the obtained solid material can be used as a raw material for the next reaction.
[0098] The black powder prepared in Example 3 was subjected to structural identification, and the results are shown in Figure 19 to Figure 27 , Fig.19 This is a transmission electron microscope image of the product obtained in Example 3 of the present invention; Fig. 20 This is an atomic force microscope image of the product obtained in Example 3 of the present invention; Fig.21 This is the X-ray diffraction pattern of the product obtained in Example 3 of the present invention; Fig. 22 This is the infrared spectrum of the product obtained in Example 3 of the present invention; Fig.23 This is a Raman spectrum of the product obtained in Example 3 of the present invention; Fig.24 The X-ray photoelectron spectrum of oxygen in the product obtained in Example 3 of the present invention; Fig.25 The X-ray photoelectron spectrum of carbon in the product obtained in Example 3 of the present invention; Fig.26 This is a high-angle annular dark-field scanning transmission microscope image of the product obtained in Example 3 of the present invention; Fig. 27 This is an energy dispersive X-ray spectrum of the product obtained in Example 3 of the present invention.
[0099] Fig.19 and Fig. 20 The atomic force microscopy image shows that the obtained product is a two-dimensional ultra-thin material; Fig.21 The X-ray diffraction pattern shows that the obtained product is a carbon material; Figures 22 to 25 It was shown that the obtained product was reduced graphene oxide; Fig.26 It shows that there are single metal atoms in the obtained products; Fig. 27 It shows that the single atoms present in the obtained product are copper single atoms. Figures 1 to 9 It can be seen that the product synthesized in Example 3 is copper single atoms supported by reduced graphene oxide.
[0100] Example 4
[0101] 7.5 g of polyethylene terephthalate and 30 g of zinc oxide powder are physically mixed to obtain a mixed solid raw material; the solid mixed raw material is loaded into a special quartz boat, and the quartz boat is placed in a reaction furnace.
[0102] Argon gas is introduced into the reactor at a flow rate of 180 mL / min to exclude air in the reactor chamber, and the air exclusion time is 3 minutes. After the air is excluded, argon gas is continuously introduced until the reaction is completed; the heating rate of the reactor is 100°C / s, the reaction temperature is 1000°C, and the reaction time is 10 minutes; after the reaction is completed, the obtained product is washed with hydrochloric acid several times to remove residual zinc ions, and filtered to separate to obtain a solid, and the obtained solid is dried in a drying oven at 80°C to obtain a black powder, i.e., zinc single atoms loaded on reduced graphene oxide; after the washing is completed, the waste liquid is recovered and dried in a drying oven at 60°C to obtain a solid material, and the obtained solid material can be used as a raw material for the next reaction.
[0103] The black powder prepared in Example 4 was subjected to structural identification, and the results are shown in Figure 28 to Figure 36 , Fig.28 This is a transmission electron microscope image of the product obtained in Example 4 of the present invention; Fig.29 This is an atomic force microscope image of the product obtained in Example 4 of the present invention; Fig.30 This is the X-ray diffraction pattern of the product obtained in Example 4 of the present invention; Fig.31 This is the infrared spectrum of the product obtained in Example 4 of the present invention; Fig.32 This is a Raman spectrum of the product obtained in Example 4 of the present invention; Fig.33 The X-ray photoelectron spectrum of oxygen in the product obtained in Example 4 of the present invention; Fig.34 The X-ray photoelectron spectrum of carbon in the product obtained in Example 4 of the present invention; Fig.35 This is a high-angle annular dark-field scanning transmission microscope image of the product obtained in Example 4 of the present invention; Fig.36 This is an energy dispersive X-ray spectrum of the product obtained in Example 4 of the present invention.
[0104] Figures 28-29 It was shown that the obtained product was a two-dimensional ultrathin material; Fig.30 The X-ray diffraction pattern shows that the obtained product is a carbon material; Figures 31-34 It was shown that the obtained product was reduced graphene oxide; Fig.35 It shows that there are single metal atoms in the obtained products; Fig.36It shows that the single atom present in the obtained product is a single zinc atom. Figure 28 to Figure 36 It can be seen that the product synthesized in Example 4 is a single zinc atom supported by reduced graphene oxide.
[0105] Comparative Example 1
[0106] 7.5 g of polyethylene terephthalate powder was ground to obtain a solid raw material; the solid mixed raw material was loaded into a special quartz boat, and the quartz boat was placed in a reaction furnace.
[0107] Argon was introduced into the reactor at a flow rate of 180 mL / min to exclude the air in the reactor chamber. The air exclusion time was 3 min. After the air was excluded, argon was continuously introduced until the reaction was completed. The heating rate of the reactor was 100°C / s, the reaction temperature was 1000°C, and the reaction time was 10 min. After the reaction was completed, the obtained product was washed several times with hydrochloric acid to remove surface impurities, and filtered to obtain a solid. The obtained solid was dried in a drying oven at 80°C to obtain a black powder.
[0108] The black powder prepared in Example 1 was subjected to structural identification, and the results are shown in Fig.37 , Fig.37 This is a transmission electron microscope image of the product obtained in Comparative Example 1 of the present invention.
[0109] Fig.37 It is shown that the obtained product is a bulk material, therefore, redox graphene cannot be obtained by heating pure plastic through a Joule heating device.
[0110] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing reduced graphene oxide loaded metal clusters / single atom materials, comprising the following steps: a) physically mixing the plastic and the metal compound to obtain a solid mixed raw material; b) rapidly pyrolyzing the solid mixed raw material in a hydrogen-free atmosphere to obtain reduced graphene oxide-supported metal clusters / single atom materials.
2. The preparation method according to claim 1, characterized in that: The plastic is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate, polycarbonate, polyvinyl chloride or polystyrene; The metal compound is selected from at least one of metal oxides, chlorides, nitrates or acetylacetonates; The metal is selected from at least one of iron, cobalt, nickel, copper, zinc, gold, silver, platinum, palladium, iridium, ruthenium or rhodium.
3. The preparation method according to claim 2, characterized in that: The plastic is plastic waste.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The mass ratio of the plastic to the metal compound is 0.05-4:
1.
5. The preparation method according to claim 4, characterized in that: The plastic is plastic particles, and the diameter of the plastic particles is 1 μm to 3 mm; The metal compound is metal compound powder.
6. The preparation method according to claim 1, characterized in that: The step b) specifically comprises the following steps: The solid mixed raw material is added into a Joule heating device, and an inert gas is introduced to exclude air; under the condition of introducing the inert gas, the solid mixed raw material is rapidly pyrolyzed in a hydrogen-free atmosphere to obtain reduced graphene oxide loaded metal clusters / single atom materials.
7. The preparation method according to claim 6, characterized in that: The inert gas is selected from argon or nitrogen; The flow rate of the inert gas is 50 mL / min to 300 mL / min.
8. The preparation method according to claim 6, characterized in that: The pyrolysis temperature is 300° C. to 1200° C., the heating rate is 50° C. / s to 2000° C. / s, and the time is 0.5 min to 15 min.
9. The preparation method according to claim 1, characterized in that: The step b) further comprises the following steps: The reaction product obtained by pyrolysis is washed and separated, and the obtained solid is dried to obtain reduced graphene oxide loaded metal clusters / single atom materials.
10. The preparation method according to claim 9, characterized in that: The washing is performed by using hydrochloric acid; the separation is performed by suction filtration; and the drying temperature is 50° C. to 100° C.